Advances in Fatigue and Fracture Testing and Modelling - Abdallah, Zak; Aldoumani, Nada (IntechOpen, 2022)
Advances in Fatigue and Fracture Testing and Modelling explores various aspects related to fatigue and fracture in metallic and non-metallic materials in terms of mechanical testing and numerical modelling. The book provides results of research work conducted by experts worldwide. It discusses fatigue failure of materials and presents possible numerical solutions. It also presents predictive models and finite element (FE) activities to illustrate the behaviour of materials in real-life conditions.